BIOSYNTHESIS OF NANOPARTICLES FROM PLANT EXTRACTS AND THEIR APPLICATIONS IN MEDICAL TREATMENTS AND DRUG DELIVERY: A REVIEW - N. A. Jdayea; E. E. Al-Abodi (مجلة الأنبار للعلوم الزراعية)
Nanotechnology is one of the modern technologies used in many fields, including agriculture, industry, and medicine. Nanoparticles are synthesized in many ways, with the biological method using microorganisms or plant extracts is among the easy, quick, cheap, and environmentally safe ways of doing. Green nanotechnology is an exciting and emerging field of technology and generation that combines the concepts of green chemistry with the advantages of sustainability and overall protection of the environmen. Green chemistry methods are suitable for producing and processing hazardous chemicals that threaten human health and the environment. This technology requires extensive experience in dealing with the raw materials, especially in the elements and metals used to transform them into nanomaterials and the resulting side effects and chemical reactions. nanotechnology has achieved a systemic breakthrough and metal nanoparticles (green nanoparticles) have received much attention due to their physiological, technological and chemical differences. Biological technology is of great importance because it produces green nanoparticles in an environmentally friendly, simple, easy, fast and cost-effective way. Phenolic amino acids, flavonoids, terpenoids, and proteins are examples of reducing and oxidizing agents. This article reviews the latest studies on the biosynthesis of metal nanoparticles using plant extracts. Researchers use extracts of various plant parts (roots, stems, leaves, fruits, fruit peels, seeds) to produce nanoparticles of many metals, the most important being silver, gold, and oxides of some metals such as iron oxide and other metal oxides. This review also discusses some examples of the use of metallic nanomaterials in treating bacterial infections, viruses, and cancerous diseases, and their widespread use in drug delivery.